Biofilm-Producing Escherichia coli with fimH Gene and Their Resistance Profiles in Catheterized Patients - Muthukumar, Vanisree; Venkata, Swapna Manjari Chilukuri; Rajangam, Seetha Lakshmi; Chaithanya, Venkata; Vajravelu, Leela Kakithakara (Anti-Infective Agents, 2026)
IntroductionUrinary tract infections (UTIs) caused by Escherichia coli are a significant healthcare concern, particularly in catheterized patients, where biofilm formation enhances bacterial survival and antibiotic resistance. Virulence factors such as the fimH gene, which encodes for adhesin proteins, play a pivotal role in biofilm formation and pathogenicity. This study aims to detect antibiotic resistance patterns, biofilm formation, and fimH gene in E. coli isolated from urine samples of catheterized patients.MethodsE. coli from urine cultures was isolated and identified through standard biochemical tests. Biofilm production by uropathogenic E. coli isolates was assessed using the microtiter plate method. The antimicrobial susceptibility of the biofilm-producing isolates was determined using the Kirby-Bauer disk diffusion method. Detection of the fimH gene (adhesin) in E. coli isolates was conducted using Polymerase Chain Reaction (PCR). The interrelations between biofilm formation, virulence gene presence, and antibiotic resistance in these isolates were analyzed.Results and DiscussionOut of 49 E. coli samples, 36 were found to be biofilm producers. These biofilm producers were categorized into strong, moderate, and weak, with 7 weak, 11 moderate, and 18 strong producers. Among these, the fimH gene was present in 27 isolates. The biofilm-producing E. coli exhibited high resistance to ampicillin, ciprofloxacin, and tetracycline.ConclusionThe fimH gene plays a crucial role in the adherence of biofilm-producing E. coli to indwelling catheters, contributing to their resistance to commonly used antibiotics
Keywords: fimH